The Central Bias in Day-to-Day Viewing (Journal of Eye Movement Research, 2016)
Eye tracking studies have suggested that, when viewing images centrally presented on a computer screen, observers tend to fixate the middle of the image. This so-called `central bias' was later also observed in mobile eye tracking during outdoors navigation, where observers were found to fixate the middle of the head-centered video image. It is unclear, however, whether the extension of the central bias to mobile eye tracking in outdoors navigation may have been due to the relatively long viewing distances towards objects in this task and the constant turning of the body in the direction of motion, both of which may have reduced the need for large amplitude eye movements. To examine whether the central bias in day-to-day viewing is related to the viewing distances involved, we here compare eye movements in three tasks (indoors navigation, tea making, and card sorting), each associated with interactions with objects at different viewing distances. Analysis of gaze positions showed a central bias for all three tasks that was independent of the task performed. These results confirm earlier observations of the central bias in mobile eye tracking data, and suggest that differences in the typical viewing distance during different tasks have little effect on the bias. The results could have interesting technological applications, in which the bias is used to estimate the direction of gaze from head-centered video images, such as those obtained from wearable technology.